2018
DOI: 10.1177/0363546518802841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsular Reconstruction With an Iliotibial Band Allograft on Distractive Stability of the Hip Joint: A Biomechanical Study

Abstract: Background: The capsular ligaments and the labral suction seal cooperatively manage distractive stability of the hip. Capsular reconstruction using an iliotibial band (ITB) allograft aims to address capsular insufficiency and iatrogenic instability. However, the extent to which this procedure may restore hip distractive stability after a capsular defect is unknown. Purpose: To evaluate the biomechanical effects of capsular reconstruction on distractive stability of the hip joint. Study Design: Controlled labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 40 publications
(83 reference statements)
2
46
0
Order By: Relevance
“…In a similar stepwise resection study, van Arkel et al devised a custom joint tester and confirmed that the lateral iliofemoral ligament provided predominant external rotational restraint, whereas the pubofemoral ligament restrained external rotation and abduction during hip extension 43 . In similar studies, the labrum and the ligamentum teres acted as secondary restraints in wider external rotations [30][31][32]42,43 , whereas the structures of the capsule, labrum, and zona orbicularis were crucial for rotational and distraction stability 16,45 . These investigations examined hips without pathology from older donors, but were among the first laboratory studies to collectively provide important clinical insights as to which ligaments were responsible for rotational stability and which to potentially release or avoid during surgery.…”
Section: Contributions To Joint Stabilitymentioning
confidence: 92%
See 4 more Smart Citations
“…In a similar stepwise resection study, van Arkel et al devised a custom joint tester and confirmed that the lateral iliofemoral ligament provided predominant external rotational restraint, whereas the pubofemoral ligament restrained external rotation and abduction during hip extension 43 . In similar studies, the labrum and the ligamentum teres acted as secondary restraints in wider external rotations [30][31][32]42,43 , whereas the structures of the capsule, labrum, and zona orbicularis were crucial for rotational and distraction stability 16,45 . These investigations examined hips without pathology from older donors, but were among the first laboratory studies to collectively provide important clinical insights as to which ligaments were responsible for rotational stability and which to potentially release or avoid during surgery.…”
Section: Contributions To Joint Stabilitymentioning
confidence: 92%
“…They noted that the anterior capsule predominantly controlled rotation and displacement, suggesting that the iliofemoral ligaments should be carefully preserved using more conservative capsulotomies. For capsular defect cases, allograft can be a viable option to restore distraction stability 15,16 . On the other hand, Hebert et al compared the effects of hip effusion (simulated with an injection of 10 mL of saline solution) and capsular tears 13 .…”
Section: Surgical Management Hip Preservation Capsulotomy and Repairmentioning
confidence: 99%
See 3 more Smart Citations